Surgical treatment of non-unions in the ulna and radius: a one-year outcome study - Findeisen, Sebastian; Maier, Katinka; Ferbert, Thomas; Tanner, Michael Christopher; Großner, Tobias; Bewersdorf, Tim; Schamberger, Christian T.; Schmidmaier, Gerhard; Böpple, Jessica C. (European journal of trauma and emergency surgery, 2025)
The incidence of non-unions of the forearm following conservative or surgical treatment of forearm fractures ranges from 2% to 5.3%. These non-unions can lead to significant limitations in the patient’s physical capabilities, necessitating an appropriate treatment plan. The aim of this study was to evaluate osseous consolidation of forearm non-unions after six months and one year as well as to assess patient-reported outcomes. A total of 36 patients with non-unions of the forearm, operatively treated in our department between 01/10 and 12/21, completed the follow-up period for this study. Radiographic evaluation was performed using the modified Lane-Sandhu Score. Osseous consolidation was assessed at six and 12 months postoperatively. Additionally, patient-reported outcomes and variations of surgical treatment were analysed. The prevalence of non-unions in our study was 30.56% for the ulna, 50% for the radius, and 19.44% for both bones. 85% of patients received bone grafts, with 48% receiving cortico-cancellous bone grafts (CCBG) and 52% receiving cancellous bone from the iliac crest or femur. In total, 67% of patients demonstrated consolidation of the non-union within six months of surgical treatment, increasing to 89% after one year. Among patients who received CCBG, 86% showed consolidation at six months, rising to 100% at one year. Additionally, patient-reported outcome measures (PROMs), including VAS and SF-12 scores, showed overall improvement. A sufficiently long follow-up period is crucial for patients with forearm non-unions. To ensure consolidation, a follow-up period of at least six months to one year is recommended. Furthermore, the use of cortico-cancellous bone grafting combined with locking compression plates (LCP) appears to be an effective technique, providing stability during the healing process and achieving satisfactory bone healing one year postoperatively.